Modern sports ethics a reference handbook - Lumpkin, Angela (Santa Barbara, Calif. ABC-CLIO, 2009)
From the Publisher: An examination of both ethical and unethical behaviors in sports designed to help readers analyze the notion that participating in sports builds character. Is it possible to teach lasting values through sports? With coverage that explores the origins of sports, ethical theories as applied to sports, and key moral issues affecting sports throughout history to the present day, Modern Sports Ethics: A Reference Handbook surveys the realm of athletics and its potential as an arena for character development.
5: Biographical Sketches -- Arthur Robert Ashe Jr -- Margaret Ann (Peggy) Kirk Bell -- William (Bill) Warren Bradley -- Avery Brundage -- Walter Byers -- Ken Carter -- Roberto Clemente -- Anita Luceete DeFrantz -- Jean Driscoll -- Joe Dumars III -- Anthony (Tony) Kevin Dungy -- Joe Ehrmann -- Fred Engh -- Henry Louis (Lou) Gehrig -- Grant Henry Hill -- Michael Terrence (Terry) Holland -- Robert (Bobby) Tyre Jones Jr -- Johann Olav Koss -- Michael (Mike) William Krzyzewski -- Richard Lapchick -- Dale Bryan Murphy -- Dikembe Mutombo -- James Naismith -- Alan Cedric Page -- Jack (Jackie) Roosevelt Robinson -- Arthur (Art) Joseph Rooney Sr -- Wilma Glodean Rudolph -- Dean Edwards Smith -- Dawn Michelle Staley -- Sharon Kay Stoll -- Charlene Vivian (Stoner) Stringer -- Jim Thompson -- LeRoy Walker -- Hazel Virginia (Hotchkiss) Wightman -- John Wooden -- 6: Data And Documents -- Youth sport -- Honor the game -- Interscholastic sports -- Extracurricular physical activity programs -- Arizona sports summit accord -- Females in sports -- Excerpts from "A Call to Action" from the Knight Commission on Intercollegiate Athletics -- Race and ethnicity -- Olympic sports -- Conclusion -- 7: Directory Of Organizations -- United States Olympic Committee and the national governing body for each sport -- Summer sports -- Winter sports -- Non-Olympic sports with national governing bodies -- Single-sport organizations -- Multi-sport organizations -- Sport-affiliated organizations -- Professional sport organizations -- 8: Print And Nonprint Resources -- Print resources -- Ethical issues in sport for all -- Ethical issues in youth sport -- Ethical issues in interscholastic sport -- Ethical issues in intercollegiate sport -- Ethical issues in international sport -- Nonprint resources -- Ethical issues in sport for all -- Ethical issues in youth sport -- Ethical issues in interscholastic sport -- Ethical issues in intercollegiate sport -- Ethical issues in international sport -- Glossary -- Index -- About the author.
Keywords: Sports -- Moral and ethical aspects